Mechanical properties of the hydroxyapatite and magnetic nanocomposite of hydroxyapatite adsorbents - Armin Vahdat; Behrooz Ghasemi; Mardali Yousefpour (South African Journal of Chemical Engineering, 2020)
In the current study, a special technique was used to prepare hydroxyapatite (HAp) and magnetic nano composite of hydroxyapatite (HAp/Fe3O4). In order to investigate the mechanical properties of the produced materials, Vickers hardness method and direct crack measurements method were used, The three point bending test was also applied to determine the bending strength. The maximum hardness under 98 N force was determined to be 750 MPa for the magnetic nanocomposite of hydroxyapatite. The crack size of the adsorbents were measured by SEM technique and the maximum KIC was reported 0.65 MPa.m1/2 for the magnetic hydroxyapatite adsorbent. Besides, the bending strength for HAp/Fe3O4 was 3.9 Mpa which was higher than the pure hydroxyapatite. It has been found that Fe3O4 nano particles can improve the mechanical properties of the hydroxyapatite adsorbent significantly.